PENERAPAN THINK PAIR SHARE BERBANTUAN KARTU SOAL UNTUK MENINGKATKAN HASIL BELAJAR KALOR DAN PERPINDAHANNYA - Tobing, Polmer Lumban; Djudin, Tomo; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to improve students' learning outcomes using Think Pair Share learning with the help of question cards about heat material and its transfer in class VII of SMP Negeri 1 Sungai Raya. The implementation consists of three stages, namely Thinking, Pairing, and Sharing. The research method used in this study is an experimental method in the form of Quasi Experimental Design with Nonequivalent Control Group Design. The sample of this study was students of class VII A as the control class and VII C as the experimental. Pretest in the experimental class obtained an average score of 39.83 and posttest of 81.29, in the control class the average pretest was obtained for 48.75 and posttest for 74.21. The results showed that there were differences in learning outcomes with Think Pair Share assisted with question cards in class VII C and with ordinary learning models in class VII A. The application of cooperative learning models with Think Pair Share assisted with question cards also showed an effect size of 1, 01 (high category). The application Think Pair Share type assisted by effective question cards to improve student learning outcomes about the heat material and its displacement.Keywords : Cooperative Learning, Learning Outcomes, Heat & Displacement, Problem Cards, Think Pair Share